Liver Dysfunction during Pregnancy and Its Association With Preterm Birth in China: A Prospective Cohort Study - Zhuang, Xun; Cui, Ai-Min; Wang, Qin; Cheng, Xiao-Yan; Shen, Yi; Cai, Wei-Hua; Li, Hai-Bo; Zhang, Sheng; Qin, Gang (EBioMedicine, 2017)
Liver dysfunction is common in pregnancy but its association with adverse pregnancy outcomes such as preterm birth (PTB) remains unclear. A prospective cohort of HBV-infected or uninfected pregnant women attending antenatal care was recruited at Nantong Maternal and Child Health Hospital between January 1, 2012, and June 30, 2016. Liver function tests (LFTs) were monitored through pregnancy. The primary outcomes were PTB and very PTB (delivery prior 37 and 32weeks' gestation respectively). Poisson regression was used to estimate adjusted risk ratios (RR) for women with HBV infection and LFT abnormalities. Among 36,755 pregnant women (1,113 HBV carriers and 35,642 non-HBV subjects), 3,519 (9.57%) had abnormal LFTs. The commonest cause for liver dysfunction during pregnancy was non-alcoholic fatty liver diseases (NAFLD, 51.3%). Abnormal aspartate aminotransferase (AST), gamma-glutamyltransferase (GGT) and two folds upper limit of normal total bilirubin (RR and 95%CI: 2.73, 1.30–5.76; 2.24, 1.35–3.31; 2.01, 1.22–3.31 respectively), rather than HBsAg positivity, were identified as independent risk factors for preterm birth. Besides, GGT abnormality was associated with increased risk of very PTB. We suggest that surveillance of LFTs among pregnant women should be warranted, given the increased risk of PTB. •Among a cohort of 36,755 pregnant women (1,113 HBV carriers, 35,642 non-HBV controls), 3,519 (9.57%) had abnormal LFT results.•Abnormal AST, GGT and total bilirubin, rather than HBsAg positivity, were independent risk factors for preterm birth.•The commonest cause for liver dysfunction during pregnancy was non-alcoholic fatty liver diseases (NAFLD). Most previous studies showed that HBV carrier status may be an independent, but only weak risk factor for preterm birth. In this prospective cohort study, we suggest that liver dysfunction, rather than HBsAg positivity, is associated with risk for preterm birth. The commonest cause for liver dysfunction during pregnancy was non-alcoholic fatty liver diseases (NAFLD). Our findings are not contradictory to previous findings, as HBV infection status may have a synergistic effect in case of premature birth. This study improves our understanding on the importance of surveillance for liver function tests among pregnant women.